LELANG JABATAN SEBAGAI KEBIJAKAN PUBLIK DALAM MEMILIH PEJABAT DAERAH DI KABUPATEN KUTAI KARTANEGARA, KALIMANTAN TIMUR TAHUN 2017 - Nanik Pujiastuti (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2018)
The researcher is willing to know the process of the position bidding .The location of the reserch is in Tenggarong.The method of it is qualitative one by obeserving, interview and library by taking the news fromthe local dailynews papers.The results of the research is that the Regent of Kutai Kartanegara will get the competitive and qualified high officers depends on the below criterias,(1).To have high competitiveness and leadership, 2).To have quick and precise to make decision,(3).Nomort tbe afraid towards the risk then to be brave in making decision in any difficulty,(4).To have selff-confidence and Nomore to be afraid to action,(5).The bidding process has to objective and high trade mark in academic level,(6).To have the skill in explaining the problem to the staff clearly and distingly .The suggestions of the researcher about the process of position bidding are (1).T do the bidding in reality nomore only just show-off,(2).To combat the colusion, corruption and nepotism ain the area here in all levels (4).Nomore discrimination anyway,(5).The offficer who is passed the test has to make a program which is practised in 100 days working if he or she fails the he or she has to resign.